Analysis of the mechanism of saponin biotransformation in Dioscoreae nipponicae rhizoma by the endophytic fungus Fusarium sp. C39 using whole‐genome sequencing. (12th April 2022) - Ding, Changhong; Yu, Dan; Chen, Yiyang; Zhu, Junyi; Wu, Junkai; Du, Xiaowei; Wang, Xijun
Abstract: Fusarium sp. C39 is an endophytic fungus of Dioscorea nipponica Makino. Symbiosis of Fusarium sp. C39 with Rhizoma Dioscoreae Nipponicae (RDN) can significantly increase the content of saponin, which provides a new approach for saponin production and reduces the pressure on natural sources of saponins. However, the underlying mechanism is not clear, limiting its application. In this study, the genome of Fusarium sp. C39 was sequenced, the gene functions were predicted via gene annotation, and the genome was compared to the genomes of four related species. Fusarium sp. C39 is predicted to encode many key enzyme genes involved in saponin synthesis, which could transform the mevalonate, isopentenyl pyrophosphate, and various intermediate compounds present in the RDN extract into saponins. The Fusarium sp. C39 genome contains specific genes that are conducive to its endophytic lifestyle and can provide abundant raw materials for saponin synthesis. Based on the genomic analysis, we proposed the mechanism by which Fusarium sp. C39 generates saponins and provides a theoretical basis for rapid, efficient, low‐cost production of saponins.